Performing the Professional Role by Teachers Who Experienced Reversing Roles in the Family - Żłobicki, Wiktor (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
It is assumed that there is a relationship between the experience of parentification, i.e., the reversal of roles in the family, and the effects of relational trauma resulting from parentification, and the nature of professional work related to broadly understood assistance. Research confirms that people choosing, for example, the profession of a teacher, doctor, psychologist, psychotherapist or nurse, have often experienced parentification in their family of origin. The aim of the study is to draw attention to possible disruptions in performing the professional role by teachers who experienced the role reversal in the family in their childhood. Taking into account the social importance of education system, it seems necessary to carry out representative empirical analyses on the effects of parentification on performing the professional role of teachers and, consequently, undertaking psychoeducational activities.
Keywords: parentification; family; teacher; professional role; interpersonal relations